Effect of Sowing Dates, Seedrate and the Fertilization on the Yield of Wheat Under Rainfed Condition in the "Haveli" (Bunded) Area of the Madhya Pradesh - Bisen, C.R.; TIWARI, B.P.; Lokras, V.G.; Rao, K.C. (Journal of Soil and Water Conservation, 2022)
Wheat is one of the major crops of the state, and 95 per cent of it is raised without irrigation. The average annual rainfall in the wheat growing, tract of the state varies from 750 to 1300 mm. In some areas of the state bunding is done to impound water during rains. After the rains the water is let out and sowing done generally without any cultivation when the soil is in workable condition. This system is called `Haveli' (locally) cultivation. There is a general belief that use of fertilizers, without irrigation, is hazardous and that the crops receiving fertilizer require more water. Stewart (1947) recommended only light dressing of nitrogen for crops grown in un-irrigated areas.